Balancing Throughput and Fair Execution of Multi-DNN Workloads on Heterogeneous Embedded Devices - Karatzas, Andreas; Anagnostopoulos, Iraklis (IEEE transactions on emerging topics in computing, 2025)
The rise of Deep Neural Networks (DNNs) has resulted in complex workloads employing multiple DNNs concurrently. This trend introduces unique challenges related to workload distribution, particularly in heterogeneous embedded systems. Current run-time managers struggle to efficiently utilize all computing components on these platforms, resulting in two major problems. First, the system throughput deteriorates due to contention on the computing resources. Second, not all DNNs are affected equally, leading to inconsistent performance levels across different models. To address these challenges, we introduce FairBoost, a framework for efficient and fair multi-DNN inference on heterogeneous embedded systems. FairBoost employs Reinforcement Learning (RL) to efficiently manage multi-DNN workloads. Additionally, it incorporates a novel numerical representation of DNN layers via a Vector Quantized Variational Auto-Encoder (VQ-VAE). Finally, it enables knowledge transfer to similar heterogeneous embedded systems without retraining and/or fine-tuning. Experimental evaluation of FairBoost over 18 DNNs and various multi-DNN scenarios shows an average throughput/fairness improvement of × 3.24 ×3.24<inline-graphic xlink:href="karatzas-ieq1-3407055.gif"/> . Additionally, FairBoost facilitates knowledge transfer from the initial platform, Orange Pi 5, to a new system, Odroid N2+, without any retraining or fine-tuning achieving similar gains.